Urinary bladder rupture during voiding cystourethrography - Kyong Ok Lee; Se Jin Park; Jae Il Shin; Suk Young Lee; Kee Hyuck Kim (Korean Pediatric Society, 2012)
Voiding cystourethrography (VCUG) is a commonly performed diagnostic procedure for the evaluation of vesicoureteral reflux with urinary tract infection or congenital renal diseases in children. The procedure is relatively simple and cost-effective, and complications are very rare. The iatrogenic complication of VCUG range from discomfort, urinary tract infection to bacteremia, as well as bladder rupture. Bladder rupture is a rare complication of VCUG, and only a few cases were reported. Bladder rupture among healthy children during VCUG is an especially uncommon event. Bladder rupture associated with VCUG is usually more common in chronically unused bladders like chronic renal failure. Presented is a case of bladder rupture that occurred during a VCUG in a healthy 9-month-old infant, due to instilled action of dye by high pressure. This injury completely healed after 7 days of operation, and it was confirmed with a postoperative cystography. The patient's bladder volume, underlying disease, velocity of the contrast media instilled, catheter size, and styles of instillation are important factors to prevent bladder rupture during VCUG. Management of bladder rupture should be individualized, but the majority of infants are treated with the operation. In conclusion, bladder rupture is a rare complication, however, delicate attention is needed in order to prevent more dire situations.